Characteristics of tropospheric ozone depletion events in the Arctic spring: analysis of the ARCTAS, ARCPAC, and ARCIONS measurements and satellite BrO observations - Koo, J.-H.; Wang, Y.; Kurosu, T. P.; Chance, K.; Rozanov, A.; Richter, A.; Oltmans, S. J.; Thompson, A. M.; Hair, J. W.; Fenn, M. A.; Weinheimer, A. J.; Ryerson, T. B.; et al. (Atmospheric Chemistry and Physics, 2012)
Arctic ozone depletion events (ODEs) are caused by halogen catalyzed ozone loss. In situ chemistry, advection of ozone-poor air mass, and vertical mixing in the lower troposphere are important factors affecting ODEs. To better characterize the ODEs, we analyze the combined set of surface, ozonesonde, and aircraft in situ measurements of ozone and bromine compounds during the Arctic Research of the Composition of the Troposphere from Aircraft and Satellites (ARCTAS), the Aerosol, Radiation, and Cloud Processes affecting Arctic Climate (ARCPAC), and the Arctic Intensive Ozonesonde Network Study (ARCIONS) experiments (April 2008). Tropospheric BrO columns retrieved from satellite measurements and back trajectory calculations are also used to investigate the characteristics of observed ODEs. In situ observations from these field experiments are inadequate to validate tropospheric BrO columns derived from satellite measurements. In view of this difficulty, we construct an ensemble of tropospheric column BrO estimates from two satellite (OMI and GOME-2) measurements and with three independent methods of calculating stratospheric BrO columns. Furthermore, we select analysis methods that do not depend on the absolute magnitude of column BrO, such as time-lagged correlation analysis of ozone and tropospheric column BrO, to understand characteristics of ODEs. Time-lagged correlation analysis between in situ (surface and ozonesonde) measurements of ozone and satellite derived tropospheric BrO columns indicates that the ODEs are due to either local halogen-driven ozone loss or short-range (∼1 day) transport from nearby regions with ozone depletion. The effect of in situ ozone loss is also evident in the diurnal variation difference between low (10th and 25th percentiles) and higher percentiles of surface ozone concentrations at Alert, Canada. Aircraft observations indicate low-ozone air mass transported from adjacent high-BrO regions. Correlation analyses of ozone with potential temperature and time-lagged tropospheric BrO column show that the vertical extent of local ozone loss is surprisingly deep (1–2 km) at Resolute and Churchill, Canada. The unstable boundary layer during ODEs at Churchill could potentially provide a source of free-tropospheric BrO through convective transport and explain the significant negative correlation between free-tropospheric ozone and tropospheric BrO column at this site.